What goes on TOA : lessons from Tāne Ora o Aotearoa (TOA) in high-performance : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy, Te Pūtahi-a-Toi, School of Māori Knowledge, Massey University, Palmerston North, New Zealand. EMBARGOED to 2 October 2026. - Rowe, Luke (Massey University, 2023)
Disproportionately high burden of disease, social exclusion and deprivation among Māori men are well documented across most health and social indices, and they are reflected within a broad range of policy, strategy, and service delivery initiatives. The reasons underpinning these inequities are certainly complex though clear, as they are connected to a suite of social, cultural, environmental, historical, and structural factors that each coalesce to undermine the overall health status of Māori men. Despite this, there is a growing population of tāne (Māori men) who continue to buck these trends. They are referred to in this thesis as, “tāne ora.” The focus on tāne ora, rather than on Māori men’s health, is deliberate and emphasises the fact that while these two concepts share similar goals and objectives, they are founded on different principles and philosophies. Like the renowned Gould et al (2002) study which interviewed 10 Olympic gold medallists revealing a number of common characteristics between them, this research is about What Drives Tāne Ora focusing on a specific subset of tāne who operate within high-performance environments. Grounded in Kaupapa Māori and Mana Tāne theories, a phenomenological and qualitative research design provided the framework for exploring the journeys of eight tāne within professional rugby aged between 20 and 36 years old. This thesis presents findings of the relationship between high-performance (one phenomena) and tāne ora (another phenomena). By taking this approach, these tāne offer insights into their childhood through to their present-day high-performance endeavours as current All Blacks and/or Māori All Blacks. Three seminal findings were established from this research. Firstly, research into the health and wellbeing of tāne requires broader emphases and attention. Not to simply perpetuate health disparities and deprivation, but to cast a light on where opportunities for gains exist and how more bespoke solutions can be developed. Secondly, health and wellbeing of tāne should be informed by research methodologies which are equally as nuanced and framed. The need for a Mana Tāne Research methodology is overdue if not desirable. Lastly, what drives tāne ora involves a complex interplay of conditions referred to in an acronym format as, MANA TANE. Notably, that any pursuits related to tāne ora needed to be mātauranga-informed, and activated by mana in the first instance. MANA TANE highlights that while all conditions are important, there are some (i.e., MANA) that are essential and others (TANE) that are complimentary. These illustrate the convergence of the conditions as an alternative pathway towards achieving tāne ora. One in which the rules of the sporting and Māori worlds are different with one being more transient and the other, enduring. And that those who are most successful are likely to be those that can have a positive relationship with both modes seamlessly.
Keywords: Māori (New Zealand people); Professional athletes; Mental health; Male athletes; Rugby football players; Health and hygiene; New Zealand; Tāne; Ora; Hauora hinengaro; Hākinakina; Toa; Kaitākaro whutupōro; Mana; Māori health; high performance; Māori knowledge; psychology; Māori Doctoral Thesis; 451019 Ngā hākinakina me te korikori tinana o te Māori (Māori sport and physical activity)